Estudio doctrinario y jurídico de la prevención social del ciberacoso de niñas, niños y adolescentes en las redes sociales - Martínez Jiménez, Alex Nikolai (2024)
This Curricular Integration or Graduation Work is entitled: "DOCTRINARY AND LEGAL STUDY OF THE SOCIAL PREVENTION OF CYBERBULLYING OF GIRLS, CHILDREN AND ADOLESCENTS IN SOCIAL NETWORKS" and has as its main objective, through a critical legal and doctrinal analysis, to demonstrate how the rights contained in the Constitution of the Republic of Ecuador in favor of girls, boys and adolescents are threatened by the exacerbated and inappropriate use of social networks and new technologies used in schools. In this work, the qualitative and quantitative paradigm was obtained because the Rights established in the Constitution of the Republic of Ecuador and in turn in the Organic Code of Childhood and Adolescence have been reviewed from a perspective of their basic qualities based on the coexistent reality of Ecuador and also its logical and doctrinal foundations have been reviewed in a cautious way, which has led to mechanizing the best solution to the problem raised. In the same way, interviews were conducted with key people within the protection of the rights of children and adolescents, who are lawyers in free practice in order to capture all the scientific and empirical information that can provide us with a viable solution. of the topic raised. In the same way, a survey and an interview have been carried out, which has allowed us to understand the public discernment about the rights of children and adolescents. It was possible to determine what the rights of children and adolescents consist of and how they work and their importance and their evident relationship with the right to life, survival and development, in clear agreement with the Doctrine of integral protection. It is established that social networks clearly threaten the rights of children and adolescents contemplated in the Constitution of the Republic of Ecuador. The proposed proposal is necessary for the protection of the rights of children and adolescents, because it mechanizes a procedure that allows to better guarantee adequate access to guarantee the rights of vulnerable care groups, especially children. and teenagers.